2006
DOI: 10.2337/diabetes.55.01.06.db05-1105
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin Multimeric Complexes and the Metabolic Syndrome Trait Cluster

Abstract: Adiponectin circulates in human plasma mainly as a 180-kDa low molecular weight (LMW) hexamer and a high molecular weight (HMW) multimer of approximately 360 kDa. We comprehensively examined the relationships between circulating levels of total adiponectin, adiponectin multimers, and the relative distribution (i.e., ratio) of multimeric forms with key features of the metabolic syndrome. Total adiponectin (r = 0.45), HMW (r = 0.47), LMW (r = 0.31), and HMW-to-total adiponectin ratio (r = 0.29) were significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

28
282
2
14

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 428 publications
(326 citation statements)
references
References 33 publications
28
282
2
14
Order By: Relevance
“…Currently available clinical data support the hypothesis that HMW adiponectin is the most physiologically relevant form [39,40]. Only HMW adiponectin shows the same strong associations with parameters of insulin sensitivity as total adiponectin [39]. This is thought to indicate that most of the reported relationships are explained largely by HMW adiponectin.…”
Section: Discussionmentioning
confidence: 87%
“…Currently available clinical data support the hypothesis that HMW adiponectin is the most physiologically relevant form [39,40]. Only HMW adiponectin shows the same strong associations with parameters of insulin sensitivity as total adiponectin [39]. This is thought to indicate that most of the reported relationships are explained largely by HMW adiponectin.…”
Section: Discussionmentioning
confidence: 87%
“…A number of recent papers highlight the relevance of the HMW form for the peripheral functions of adiponectin [19,[25][26][27][28][29][30]. In light of the very large size of this complex (>500 kDa), it is not surprising that the HMW form is very inefficiently translocated across the BBB and not found in any measurable quantities in CSF.…”
Section: Discussionmentioning
confidence: 99%
“…In obesity and diabetes, low plasma adiponectin concentrations are related to the degree of hyperinsulinaemia and the severity of insulin resistance [11][12][13]. Adiponectin and HMW adiponectin levels are negatively correlated with serum triglycerides and positively with HDL particles [14,15]. The mechanisms mediating adiponectin-lipid interactions remain unknown but it is suggested that HMW adiponectin plays a prominent role in the metabolic changes [15,16].…”
Section: Introductionmentioning
confidence: 99%